Kajian Etnobotani Tanaman Hanjuang (Cordyline fruticosa) pada Wawatjan Babad Sumedang - Fauzan Ahmad Wijaya (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
Wawatjan Babad Sumedang is one of the ancient texts telling about the struggle of Prabu Geusan Ulun in defending and taking responsibility for Sumedang from the Cirebon attack as a result of the love between him and Harisbaya, the empress of Cirebon. In one part of this chronicle, the Hanjuang was planted by a character named Embah Djaja Perkosa. It is the background for the study of the manuscript from an ethnobotanical perspective. This study uses qualitative methods with data collection techniques through interviews, observation, and literature studies. Interviews were conducted in a semi-structured and snowball-sampling manner with community leaders. Furthermore, observation was carried out by visiting the Hanjuang Kutamaya complex in Padasuka Village, North Sumedang District, Sumedang Regency, West Java. While the literature study was performed on related references, especially the Wawatjan Babad Sumedang Manuscript. Hanjuang is mentioned in the text in verses 148, 149, 171, and 172. Hanjuang itself is a siloka of "hayu urang berjuang" or "let's fight" . In the written text, the word ngalakai is a sign that the Hanjuang needs an appropriate environment to live in. This suitable environment is filled with the flourishing of Kutamaya thanks to the existence of the river there. In addition, the process of planting Hanjuang in the events in the script is done by stem cuttings. However, the Hanjuang side as an indicator has not been resolved in this study, so further research is needed on this matter